ASSESSMENT OF THE SOCIAL BURDEN ON PATIENTS WITH PRIMARY OPEN-ANGLE GLAUCOMA - Velkovski, Zoran; Belevska, Maja; Dastevska, Emilija (Acta medicae Medianae, 2022)
Glaucoma is a chronic ophthalmic disease characterized by progressive, irreversible loss of visual acuity, long-term progression and lifelong treatment, declining work ability and self-sufficiency, which can generate social burden in patients. The study is designed to understand the social, clinical and pharmacological aspects of assessing the social burden of primary open-angle glaucoma. It is a cross-sectional study with a quantitative analytical approach, which includes 182 male and female patients with primary open-angle glaucoma, aged 20-67, with preserved visual acuity > 6/18 (0.33), according to the ICD-10 classification, conducted in the period August-November 2020 on the territory of North Macedonia. Fifty-three point three percent of the respondents were female and 46.7% male, of whom 79.12% were treated with prescribed medications, 8.8% with laser and 12.08% underwent a surgical procedure. Fifty-seven point sixty-nine percent of the respondents received treatment regularly, which in 43.96% had a negative outcome, partial success in 30.22%, and in 25.82%, the treatment prevented further vision loss. Fourteen point twenty-eight percent of the respondents experienced a social family burden and 34.07% discomfort, depression, anxiety, hopelessness and other psychosocial disorders. Primary open-angle glaucoma generates a significant socio-economic burden as a result of irreversible visual impairment, reduced work ability and productivity, and high treatment costs of patients. The degree of the social burden depends on the evolvement and clinical stage of the disease, the percentage of preserved vision, availability, manner and regularity of treatment and socio-demographic parameters such as gender, age, occupation, genetic predisposition, comorbid conditions, family history, etc. which in glaucoma play the role of predisposing risk factors.